Social and Organizational Developments Through Emerging E-Government Applications
DOI: 10.4018/978-1-60566-918-2.ch002
|View full text |Cite
|
Sign up to set email alerts
|

Unclassified Information Sharing and Coordination in Security, Stabilization, Transition and Reconstruction Efforts

Abstract: The emergence of new doctrine is enabling security, stabilization, transition and reconstruction (SSTR) operations to become a core U.S. military mission. These operations are now given equal priority to combat operations. The immediate goal in SSTR is to provide the local populace with security, restore essential services, and meet humanitarian needs. The long-term goal is to help develop indigenous capacity for securing and providing essential services, therefore, many SSTR operations are best performed by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Public agencies and organizations that operate the CI upon which society depends should be subject to audits to ensure they are meeting reasonable standards according to their industry. We must also increase the pool of reliable information by declassifying more information (Quigley, 2009;Gordon, 2010) and encouraging greater cooperation between military and civilian operations in order to develop a more nuanced understanding of risks, as opposed to more extreme ones characterized by many cybersecurity specialists (Mittu et al, 2008).…”
Section: Behaviour Modificationmentioning
confidence: 99%
“…Public agencies and organizations that operate the CI upon which society depends should be subject to audits to ensure they are meeting reasonable standards according to their industry. We must also increase the pool of reliable information by declassifying more information (Quigley, 2009;Gordon, 2010) and encouraging greater cooperation between military and civilian operations in order to develop a more nuanced understanding of risks, as opposed to more extreme ones characterized by many cybersecurity specialists (Mittu et al, 2008).…”
Section: Behaviour Modificationmentioning
confidence: 99%
“…79,120 However, several articles also highlighted the use of social media by the public to exchange information and communicate amongst themselves. 33,56,62,73,82 We also found that social media tools were used by disaster response professionals to collect data on the needs and behaviors of the public. 24,56,61,78,81 Liu 2011, for example, analyzed how an app utilizing Twitter and global positioning system can inform disaster responders about where to prioritize critical response resources.…”
Section: Social Mediamentioning
confidence: 99%